The dimensions of mastery questionnaire in school-Aged children with congenital Hemiplegia: Test-retest reproducibility and parent-child concordance - Miller, L.; Marnane, K.; Ziviani, J.; Boyd, Roslyn (2014)
Aim: To examine internal consistency, test-retest reproducibility, and parent-child concordance of the Dimensions of Mastery Questionnaire 17.0 (DMQ) in school-Aged children with congenital hemiplegia. Method: Forty-two children (8.24 ± 2.38 years, Manual Ability Classification System (MACS) I = 23, MACS II = 19) and their parents completed the DMQ, and a subset on two occasions 2-30 days apart (n = 27). Cronbach's alpha (a), intraclass correlation coefficients (ICCs), standard error of measurement (SEM), and 95% limits of agreement were calculated. Results: Internal consistency for child self-report was variable (a = 0.57-0.90). Cronbach's alphas for parent proxy report were good (a = 0.69-0.86). Test-retest reproducibility for instrumental aspect (ICC = 0.86) and total motivation (ICC = 0.84) were excellent with subscales ranging from 0.70 to 0.91. The SEM for total motivation was 0.23 points. Parent-child concordance was poor across all scores (ICC = -0.04 to 0.42) with a large SEM (0.50-0.91). Interpretation: The DMQ parent report has good test-retest reproducibility for subscales, instrumental, and total motivation scores in school-Aged children with congenital hemiplegia. Parent-child concordance was low highlighting differences in individual and contextual perspectives. © 2014 Informa Healthcare USA, Inc.